Ольвийские древности. Сборник научных трудов памяти В.М. Отрешко (1949—1999) - Скржинська, М.В. (Археологія, 2011)
Рецензія на: Ольвийские древности. Сборник научных трудов памяти В.М. Отрешко (1949—1999). — К.: ІА НАНУ — 2009. — 384 с.
.